2020
DOI: 10.1186/s13048-020-00751-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of heavily treated ovarian clear cell carcinoma with ARID1A mutations after pembrolizumab and bevacizumab combination therapy: a case report

Abstract: Background Patients with ovarian clear cell carcinoma (OCCC) have a poor prognosis because they show low sensitivity to platinum-based chemotherapy. New treatments for refractory OCCC are urgently needed. Case presentation We present a patient with refractory OCCC in whom conventional chemotherapy failed. Cachexia was induced by the disseminating recurrent tumors. Tumor tissue staining and genomic analysis revealed PD-L1 negativity, a low tumor bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Clinical trials and case reports suggest immune therapy; however, biomarker development to predict response to checkpoint inhibitor therapy has been challenging without consistent predictors (e.g., PD-L1 score) [ 94 ]. MMRd with a high tumor mutation burden and neoantigen expression are predictors of response to immune checkpoint blockade but do not explain all responsive cases.…”
Section: Molecular Subtypes Of Ovarian Carcinomasmentioning
confidence: 99%
“…Clinical trials and case reports suggest immune therapy; however, biomarker development to predict response to checkpoint inhibitor therapy has been challenging without consistent predictors (e.g., PD-L1 score) [ 94 ]. MMRd with a high tumor mutation burden and neoantigen expression are predictors of response to immune checkpoint blockade but do not explain all responsive cases.…”
Section: Molecular Subtypes Of Ovarian Carcinomasmentioning
confidence: 99%
“…Therefore, the combination of antiangiogenic drugs with other regimes might be a promising treatment strategy. A patient with refractory OCCC reached complete remission after nine cycles of pembrolizumab and bevacizumab combination therapy 42. Moreover, a retrospective real-world study showed that adding bevacizumab to chemotherapy in recurrent OCCC resulted in a remarkable benefit compared with high-grade serous ovarian carcinoma (PFS: 20 m vs 14 m) 43.…”
Section: Discussionmentioning
confidence: 99%
“…A patient with refractory OCCC reached complete remission after nine cycles of pembrolizumab and bevacizumab combination therapy. 42 Moreover, a retrospective real-world study showed that adding bevacizumab to chemotherapy in recurrent OCCC resulted in a remarkable benefit compared with high-grade serous ovarian carcinoma (PFS: 20 m vs 14 m). 43 Overall, antiangiogenic drug-containing regimens tend to be more effective in recurrent OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that the lack of prognostic significance for ARID1A does not discount continued development of direct targeting, synthetic lethal strategies, and/or investigation into predictive value of ARID1A for immune-modulatory therapies [72][73][74][75]. As one of the most prevalent biomarkers in EAOCs it is a potentially high value biomarker with mechanisms of action that may be dependent on molecular context of the cancer (and subtype) in which alterations occur.…”
Section: Discussionmentioning
confidence: 99%